Canadian Consensus Recommendations on the Management of MET-Altered NSCLC - Parneet K. Cheema; Shantanu O. Banerji; Normand Blais; Quincy S.-C. Chu; Patrice Desmeules; Rosalyn A. Juergens; Natasha B. Leighl; Brandon S. Sheffield; Paul F. Wheatley-Price; Barbara L. Melosky (Current Oncology, 2021)
In Canada, the therapeutic management of patients with advanced non-small cell lung cancer (NSCLC) with rare actionable mutations differs between provinces, territories, and individual centres based on access to molecular testing and funded treatments. These variations, together with the emergence of several novel mesenchymal-epithelial transition (MET) factor-targeted therapies for the treatment of NSCLC, warrant the development of evidence-based consensus recommendations for the use of these agents. A Canadian expert panel was convened to define key clinical questions, review evidence, discuss practice recommendations and reach consensus on the treatment of advanced MET-altered NSCLC. Questions addressed by the panel include: 1. How should the patients most likely to benefit from MET-targeted therapies be identified? 2. What are the preferred first-line and subsequent therapies for patients with MET exon 14 skipping mutations? 3. What are the preferred first-line and subsequent therapies for advanced NSCLC patients with de novo MET amplification? 4. What is the preferred therapy for patients with advanced epidermal growth factor receptor (EGFR)-mutated NSCLC with acquired MET amplification progressing on EGFR inhibitors? 5. What are the potential strategies for overcoming resistance to MET inhibitors? Answers to these questions, along with the consensus recommendations herein, will help streamline the management of MET-altered NSCLC in routine practice, assist clinicians in therapeutic decision-making, and help ensure optimal outcomes for NSCLC patients with MET alterations.